Factors propelling the intention to adopt of tobacco-free policy among employees in higher education institution - Abdul Manan, Kamaruzzaman (2018)
Higher education institutions are the best platform in emphasising health communication message and promoting healthy lifestyle. This because of its role as a centre of knowledge and character development, higher education institutions employees should have good physical and mental health in order to be able to demonstrate good values. Thus the Social Cognitive Theory (SCT) was selected specifically to takes a close look at how conducive environment, self efficacy and knowledge influence the employees’ intention towards the policy. This study used the partial least squares (PLS) and structural equation modelling (SEM) software to examine factors influencing adoption of tobacco-free policy among employees in Malaysian higher education. It also measures the impact of workplace health promotion on employee’s intention to comply with tobacco cessation regulations. Statistical results confirm that that all three constructs of employees environment, self efficacy and knowledge significantly influenced employees’ intention to adopt the tobacco free policy. The results, has also contributed to a better understanding of how effective is the higher education institutions tobacco-free policy in Malaysia. Findings are useful for policy makers, higher education institutions and practitioners to enhance Malaysian tobacco cessation. Limitations and suggestions for future research are also included.